2005
DOI: 10.2337/diacare.28.12.2896
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Monochromatic Infrared Energy on Sensation in Patients With Diabetic Peripheral Neuropathy

Abstract: OBJECTIVE -The purpose of this study was to determine the effect of monochromatic infrared energy (MIRE) on plantar sensation in subjects with diabetic peripheral neuropathy.RESEARCH DESIGN AND METHODS -In this randomized, double-blind, placebocontrolled study, 39 subjects with diabetic peripheral neuropathy completed the 8-week study. Subjects received 30 min of active or placebo MIRE three times a week for 4 weeks. Plantar sensation was tested with monofilaments at the beginning of the study (M1), following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 27 publications
(35 reference statements)
2
46
0
2
Order By: Relevance
“…However, compared to previous research, although the present study provided greater photo energy per treatment, the total duration of treatment was shorter in our study (2 weeks versus 4 weeks to 3 months). 7,18 In addition, our study provided fewer treatment sessions than those of other studies (6 sessions versus 12-90 sessions). 7,18 The effects of phototherapy are time dependent.…”
mentioning
confidence: 49%
See 3 more Smart Citations
“…However, compared to previous research, although the present study provided greater photo energy per treatment, the total duration of treatment was shorter in our study (2 weeks versus 4 weeks to 3 months). 7,18 In addition, our study provided fewer treatment sessions than those of other studies (6 sessions versus 12-90 sessions). 7,18 The effects of phototherapy are time dependent.…”
mentioning
confidence: 49%
“…7,18 In addition, our study provided fewer treatment sessions than those of other studies (6 sessions versus 12-90 sessions). 7,18 The effects of phototherapy are time dependent. 6 The MIRE therapy initiates the release of NO, with subsequent biochemical and physiological changes.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…However, the results of clinical studies are mixed. In a randomized clinical trial (RCT) by Clifft et al (8), MIRE did not provide improvement in peripheral sensation compared with sham treatment. In contrast, RCTs by Leonard et al (4) and Arnall et al (6) reported a significant improvement in peripheral sensation with MIRE.…”
mentioning
confidence: 96%